2005
DOI: 10.1093/jat/29.3.182
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of UV, Fluorescence, and Electrochemical Detectors for the Analysis of Formaldehyde-Induced DNA Adducts

Abstract: ]A high-performance liquid chromatography (HPLC) method for normal and formaldehyde-modified deoxynucleosides after hydrolysis of exposed and unexposed human placental DNA was compared with ultraviolet (UV), fluorescence (FL), and electrochemical (EC) detectors. The lower quantifiable limits (LQL) for UV detection at 254 nm were 10-22 pmol for N~-hydroxymethyldeoxyadenosine {N6-dA), N2-hydroxymethyldeoxyguanosine (N2-dG), and N4-hydroxymethyldeoxycytidine (N4-dC), with N4-dC having the highest LQL and the 2 pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2008
2008
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
5
1
Order By: Relevance
“…Previous studies show that N 6 -hydroxymethyl-dA is a primary formaldehyde-induced DNA monoadduct. Surprisingly, our data did not support the formation of detectable amounts of [ 13 CD 2 ]- N 6 -hydroxymethyl-dA from exogenous formaldehyde in cell culture. The detection limit of N 6 -methyl-dA was more sensitive than that of N 2 -methyl-dG, so a lack of sensitivity does not account for our inability to detect exogenous [ 13 CD 2 ]- N 6 -hydroxymethyl-dA.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Previous studies show that N 6 -hydroxymethyl-dA is a primary formaldehyde-induced DNA monoadduct. Surprisingly, our data did not support the formation of detectable amounts of [ 13 CD 2 ]- N 6 -hydroxymethyl-dA from exogenous formaldehyde in cell culture. The detection limit of N 6 -methyl-dA was more sensitive than that of N 2 -methyl-dG, so a lack of sensitivity does not account for our inability to detect exogenous [ 13 CD 2 ]- N 6 -hydroxymethyl-dA.…”
Section: Discussioncontrasting
confidence: 92%
“…Several previous in vitro studies have shown that N 6 -hydroxymethyl-dA is a primary formaldehyde-DNA monoadduct. Here, we examined the possible formation of N 6 -hydroxymethyl-dA in cells exposed to different doses of formaldehyde, as shown in Figure . Figure A and B gives the LC-ESI-MS/MS-SRM chromatograms of N 2 -methyl-dG in cells exposed to 0.5 mM or 1 mM [ 13 CD 2 ]-formaldehyde for 3 h, while Figure C and D shows the typical chromatograms of N 6 -methyl-dA in cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems likely that oxidation of morphine takes place at the phenolic oxygen at position 3, making it electrochemically active. This means that it is possible to use HPLC-EC, which usually has a higher sensitivity for some drugs (17), including morphine. In this study, a solid phase extraction method was used for morphine.…”
Section: Discussionmentioning
confidence: 99%
“…The structures of formaldehyde-induced DNA adducts in vitro have been known for decades [9396] and include the unstable DNA adducts N 2 -hydroxymethyl-deoxyguanosine ( N 2 -HOMe-dG), N 6 -hydroxymethyl-deoxyadenosine ( N 6 -HOMe-dA), and N 4 -hydroxymethyl-deoxycytosine ( N 4 -HOMe-dC) [118120]. N 2 -HOMe-dG is the main DNA mono-adduct induced by inhaled formaldehyde, which together with DNA protein crosslinks and toxicity-induced cell proliferation are thought to play important roles in mutagenesis and carcinogenesis.…”
Section: Formaldehydementioning
confidence: 99%